Safety Requirements Analysis using Misuse Cases Method - Ryo Alif Ramadhan; Dana Sulistyo Kusumo; Jati Hiliamsyah Husen (International Journal on Information and Communication Technology (IJoICT), 2021)
Safety requirements analysis is an activity inside software requirements engineering that focuses on finding and solving safety gaps inside a software product. One method to do safety requirements analysis is misuse cases, a technique adopted from the security analysis method. Misuse cases provide a safety analysis approach which allows detailed steps from different stakeholders' perspective. In this research, we evaluate the misuse cases method's understandability by implementing it to analyze safety requirements for an electric car's autopilot system. We assessed the developed models using the walkthrough method. We found differences between how the model understood from someone with experience in software development and those who don't.